Elite football players of Bosnia and Herzegovinian and Kosovian clubs and differences in the morphological characteristics and body composition among them - Vasiljevic, I.; Bjelica, D.; Gardasevic, J.; Bubanja, M.; Corluka, M.; Arifi, F.; Sermaxhaj, S. (Journal of Anthropology of Sport and Physical Education, 2021)
The goal of this research was to determine the differences in the morphological characteristics and body composition among the top football players of the two clubs, Bosnia and Herzegovinian football club Zrinjski Mostar and Kosovian football club Besa Peje. A sample of 46 subjects was divided into two sub-samples. The first sub-sample of the subjects consisted of 28 players of CSC Zrinjski Mostar of the average age 24.36±4.14, the champion of the Bosnia and Herzegovina in the season 2016/17, while the other sub-sample consisted of 18 players of FC Besa Peje of the average age of 21.83±3.17, the winner of Kosovo Cup in the season 2016/17. Football players were tested immediately after the end of the competition season 2016/17. Morphological characteristics in the body composition were evaluated by a battery of 11 variables: body height, body weight, waist circumference, triceps skinfold, biceps skinfold, back skinfold, abdominal skinfold, body mass index, fat percentage and muscle mass. The differences between the players of the top two football clubs in the morphological characteristics and variables for assessing body composition was determined by a t-test for independent samples. It was found that the football players of CSC Zrinjski and FC Besa Peje have statistically significant differences by the three variables that estimate the body weight, waist circumference and muscle mass.